Lateral Habenula Gone Awry in Depression: Bridging Cellular Adaptations With Therapeutics - Nuno-Perez, Alvaro; Tchenio, Anna; Mameli, Manuel; Lecca, Salvatore (Frontiers in Neuroscience, 2018)
Depression is a highly heterogeneous disease characterized by symptoms spanning from anhedonia and behavioral despair to social withdrawal and learning deficit. Such diversity of behavioral phenotypes suggests that discrete neural circuits may underlie precise aspects of the disease, rendering its treatment an unmet challenge for modern neuroscience. Evidence from humans and animal models indicate that the lateral habenula (LHb), an epithalamic center devoted to processing aversive stimuli, is aberrantly affected during depression. This raises the hypothesis that rescuing maladaptations within this nucleus may be a potential way to, at least partially, treat aspects of mood disorders. In this review article, we will discuss pre-clinical and clinical evidence highlighting the role of LHb and its cellular adaptations in depression. We will then describe interventional approaches aiming to rescue LHb dysfunction and ultimately ameliorate depressive symptoms. Altogether, we aim to merge the mechanistic-, circuit- and behavioral-level knowledge obtained about LHb maladaptations in depression to build a general framework that might prove valuable for potential therapeutic interventions.